Research on the Application of BIM Technology in Intelligent Construction of Engineering Projects - Guo, Zongxian (Transactions on Engineering and Technology Research, 2024)
Building Information Modeling (BIM) is a rapidly evolving technology that improves the efficiency and effectiveness of building design and construction processes. This study focuses on the practical application of BIM technology in engineering construction, especially in the construction of intelligent buildings. Relevant research is carried out through the intelligent management of BIM technology in all aspects of site layout and construction schedule. This paper is based on the application of BIM technology in site layout and the Internet plus application platform of BIM technology in the construction progress of actual engineering projects. This paper discusses the advantages of applying BIM technology to intelligent construction in actual engineering projects, and finds that using BIM technology to create construction sites can greatly reduce labor, time and cost. The combination of BIM platform and intelligent construction allows for closer cooperation between different engineering teams on a project, thereby improving work efficiency. By comparing the advantages and disadvantages of different BIM modeling software in intelligent construction, a construction scheme that is most suitable for engineering projects can also be obtained. The development trend of civil engineering in the future is the deep application of BIM technology in intelligent construction. In-depth research and promotion of the application of BIM in intelligent construction is of great significance to promote the progress of the entire construction industry.